Enhancing Kindergarten Teachers’ Commitment through Psychological Capital: The Mediating Role of Meaning of Work and the Moderating Influence of Principal Leadership and Compassion - Sayidah Aulia ul Haque; Koko Srimulyo; Fendy Suhariadi; Eko April Ariyanto (Journal of Educational, Health and Community Psychology, 2026)
High teacher turnover and increasingly complex professional demands in early childhood education highlight the need to strengthen kindergarten teachers’ commitment. This study tested whether psychological capital predicts teacher commitment indirectly through meaning of work and examined the moderating roles of compassion and principal leadership practices on the meaning of work–commitment association. Data were obtained from 540 kindergarten teachers nested within 176 schools using multistage random sampling and analyzed using multilevel modeling. Psychological capital significantly predicted meaning of work (β = 0.343, p < .001), and meaning of work significantly predicted teacher commitment (β = 0.385, p < .001). The indirect effect of psychological capital on commitment through meaning of work was also significant (indirect effect = 0.132, p = .008). In contrast, the interaction terms for principal leadership practices × meaning of work (β = 0.273, p = .117) and compassion × meaning of work (β = −0.101, p = .277) were not significant. Overall, the findings underscore teachers’ psychological resources and perceived work meaning as key correlates of commitment in early childhood education, while the hypothesized strengthening roles of compassion and leadership practices were not supported in this model. The results are broadly consistent with Social Cognitive Theory and suggest that interventions cultivating psychological capital and enhancing work meaning may help foster sustained teacher commitment.